Opposition to Louis XIV : the political and social origins of the French Enlightenment. - Rothkrug, Lionel (Princeton legacy library., 1965)
In tracing the history of the anti-mercantilist movement, the author shows that many of the ideas and attitudes associated with eighteenth century philosophes were first formulated in the anti-mercantilist criticism. Originally published in 1965. The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These editions preserve the original texts of these important books while presenting them in durable paperback and hardcover editions. The goal of the Princeton Legacy Library is to vastly increase access to the rich scholarly heritage found in the thousands of books published by Princeton University Press since its founding in 1905.